Understanding the Impact of Disability on Dietary Intake and Patterns in People with Multiple Sclerosis - Venasse, Myriam (Université d'Ottawa / University of Ottawa, 2019)
As current treatments for multiple sclerosis (MS) do not prevent the accumulation of long-term disability, researchers and persons with MS are interested in wellness behaviours and how they may be used to manage MS. This thesis includes a review of the literature on wellness-based interventions in persons with progressive MS. Following this review, a cross-sectional study was conducted to characterize dietary intake by disability status in this population, and to examine the functional and symptomatic correlates of dietary behaviours. Participants with MS and matched controls completed questionnaires and a three-day food intake record. There were significant differences in dietary intake with and without supplements between the MS and control groups. Correlates of dietary behaviours were also examined. Further research examining dietary intake in MS is necessary to understand how disability and other factors impact dietary intake behaviours, and which other correlates may be useful targets for future nutrition interventions.
Keywords: Multiple sclerosis; Diet; Disability